Survival Stability of RoPax Reviewed In Terms of The Water on Deck (WoD) - Hasanudin; Yulianto, Ardi Nugroho; Zubaydi, Achmad; Aryawan, Wasis Dwi (International Journal of Marine Engineering Innovation and Research, 2025)
RoPax vessels are widely used worldwide but contribute to numerous fatalities. Accidents result from human factors, vessel damage, management, and natural causes. Vessel stability is a significant concern, with WoD leading to increased load and rising KG, potentially causing capsizing. This study examines a RoPax OCD UFP that experienced a WoD-related accident in Indonesian waters. Modifications considered are standard freeing ports, becoming RoPax OCD SFP, and applying side casings, or RoPax OCD WS assessed the Stockholm Agreement. Fluid simulation and stability failure criteria were employed at varying wave heights. The largest RAO on the variation of heading angle is changed into stability criteria, resulting in realistic outcomes that have not been seen in earlier research. The highest RAO roll occurs at a heading encounter angle of 60 degrees with a value of 2.192362 degrees/m. Results show survival for RoPax UFP, RoPax SFP, and RoPax WS in the 0-1 m wave height range, with only RoPax UFP capsizing at 2-3 m. RoPax WS has an extended stability arm but decreases stability at high wave heights. RoPax SFP is unaffected by WoD but may still face capsizing depending on the pure stability arm GZ factor. Modifying RoPax UFP to RoPax SFP or RoPax WS can improve survival intact stability.